A Bibliometric Analysis of Entrepreneurial Thinking Research in Science Education from 2014 to 2023 - Latip, Abdul; Abdullah, Norazilawati; Kadarohman, Asep; Hernani, Hernani; Musa'adah, Siti (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
This research aims to provide a bibliometric literature review regarding the trends of entrepreneurial thinking (ET) research in science education in 2014-2023. In this research, five main stages were carried out in bibliometric literature: determining topics and keywords, searching databases according to keywords, refining the database, compiling statistical data, and analyzing data. Search results from the scopus.com document database using the keywords